Sekulariseringen som vilkår for kirkens arbejde - Iversen, Hans Raun (Dansk Teologisk Tidsskrift, 2010)
Secularization can be seen as a part of the modern differentiation of spheres in society or as a result of a regression of religious beliefs and practices among common people. According to Taylor’s opus magnum A Secular Age (2007) the process of secularization has four tracks of development: Most fundamental is (1) disembodiment, social disembeddedness and thereby the excarnation of religion. To this is added (2) a shift from porous to buffered selves, (3) the dissolution of holiness and (4) the existential acceptance of an immanent frame. For the individual, secularization means moving from a religiously authorized, integrated world into an open world with broken horizons for human identity. Secularization is thus not primarily about the disappearance of religion but about radical new conditions for human life – and hence for the work of the church. This applies in specific ways to the specific case of Denmark.